2003
DOI: 10.1063/1.1621071
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of nonepitaxially grown double-layered FePt:C/FeCoNi thin films for perpendicular recording

Abstract: A noneptaxially grown double-layered thin-film medium of nanocompsite FePt:C with a FeCoNi soft underlayer for high-density perpendicular magnetic recording was fabricated and investigated. Square-shaped perpendicular loops with a remanance ratio nearly equal to one and a coercivity as large as 8.5 kOe were obtained for this ordered FePt:C double-layered medium. The formation of the ordered L10 phase is confirmed by electron diffraction experiments. Transmission electron microscope observations reveal that FeP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 10 publications
1
66
0
Order By: Relevance
“…Recently, non-epitaxially grown, highly (0 0 1)-textured L1 0 FePt [9,10] and FePt based fi lms [18] have been obtained by using multilayer deposition plus post annealing. It is found that orientations of FePt grains are affected by many preparation parameters, such as initial as-deposited fi lm structure, composition, annealing time and so on [19,20]. Fig.…”
Section: Fept(cf X ) Core-shell Nanoclusters With C Matrixmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, non-epitaxially grown, highly (0 0 1)-textured L1 0 FePt [9,10] and FePt based fi lms [18] have been obtained by using multilayer deposition plus post annealing. It is found that orientations of FePt grains are affected by many preparation parameters, such as initial as-deposited fi lm structure, composition, annealing time and so on [19,20]. Fig.…”
Section: Fept(cf X ) Core-shell Nanoclusters With C Matrixmentioning
confidence: 99%
“…The loop shows perpendicular anisotropy with square shape in the perpendicular direction due to the preferential FePt L1 0 (0 0 1) texture. The perpendicular loop shows large coercivity (H c = 6.2kOe) and high remanence ratio (S=0.9) [20].…”
Section: Fept(cf X ) Core-shell Nanoclusters With C Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…The requirement of narrow size distribution can be met by creating particles with a gas aggregation cluster deposition system [1]. Crystallographic texturing of clusters could be of great use in perpendicular magnetic recording and can readily be done by multi-layer sputter deposition and annealing [2]. Depending on the choice of matrix, the final goal of decoupled grains is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The multilayering of Fe/ Pt and dimensions of the Fe and Pt individual layers, annealing temperature and time, total film thickness, alloy composition, etc., appear to play an important role in obtaining the films with c axis perpendicular to the film plane. 3,4 Recent modeling results suggested that the media for future 1 Tbit/ in. 2 should have small grain size ͑d ϳ 4 nm͒ and narrow distribution ͑ / d ϳ 0.07͒, moderate anisotropy ͑H k ϳ 25 kOe͒, coercivity ͑H c ϳ 5-8 kOe͒, and saturation magnetization ͑M s ϳ 750 emu/ cc͒.…”
Section: Introductionmentioning
confidence: 99%